Effect of using mannan-oligosaccharides and β-glucans as feed additives on growth, biochemical parameters, and immunity of Salmonella enterica serovar Enteritidis-challenged turkey - Shimaa A. Amer; Rehab I. Hamed; Gehan K. Saleh; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Ahmed Gouda; Rania M. Ibrahim; Nehal M. Nabil; Maram M. Tawakol; Momen M. Aladl; Walaa A. El-Sayed; Mohamed A. Mahmoud; et al. (Veterinary Research Communications, 2026)

Assessment of a novel floating humidification-dehumidification desalination system utilizing an air sparging and submerged dehumidifier - Nabil A.S. Elminshawy; Sodfa Diab; D.G. El-Damhogi; Yassen El.S. Yassen; Nehal M. Ashoor; Mohamed S. Soliman (Desalination, 2025)

Modulatory Effect of Competitive Exclusion on the Transmission of ESBL E. coli in Chickens - Amera F. Ebrahem; Azza S. El-Demerdash; Rania M. Orady; Nehal M. Nabil (Probiotics and Antimicrobial Proteins, 2024)
The extensive use of antimicrobial agents in broiler farms causes the emergence of antimicrobial resistance of E. coli producing severe economic losses to the poultry industry; therefore, monitoring the transmission of ESBL E. coli is of great significance throughout broiler farms. For this reason, we investigated the efficiency of competitive exclusion (CE) products to control the excretion and transmission of ESBL-producing E. coli in broiler chickens. Three hundred samples from 100 broiler chickens were screened for the incidence of E. coli by standard microbiological techniques. The overall isolation percentage was 39% and differentiated serologically into ten different serotypes: O158, O128, O125, O124, O91, O78, O55, O44, O2, and O1. The isolates represented absolute resistance to ampicillin, cefotaxime, and cephalexin. The effectiveness of CE (commercial probiotic product; Gro2MAX) on ESBL-producing E. coli (O78) isolate transmission and excretion was studied in vivo. The results showed that the CE product has interesting properties, making it an excellent candidate for targeted drug delivery by inhibiting bacterial growth and downregulating biofilm, adhesins, and toxin-associated genes loci. The histopathological findings demonstrated the capability of CE in repairing internal organ tissues. Our outcomes suggested that the administration of CE (probiotic products) in broiler farms could be a safe and alternative approach to control the transmission of ESBL-producing virulent E. coli in broiler chickens.

Effects of dietary nano-selenium supplementation on Riemerella anatipestifer vaccinated and challenged Pekin ducklings (Anas platyrhynchos) - Abdelfattah H. Eladl; Nehal M. Nabil; Amal Awad; Shereen Badr; Amera F. Ebrahem; Maram M. Tawakol; Enas Hammad; Hanaa S. Ali; Reham A. El-Shafei (Veterinary Microbiology, 2023)